Three essays on livestock biosecurity and traceability - Mitchell, James L. (Kansas State University, 2020)
Chapter 1: The Effects of Production Contracts on Biosecurity Adoption by United States Hog Producers. Production contracts play an important role in U.S. livestock production. As their use has grown, so has the need to understand their influence on production practices. Understanding the link between production contracts and health management practices, for example, is crucial to policies and analysis of the preparation for, and potential consequences of larger scale animal disease outbreaks in the United States. The benefits and costs, as well as tolerance for disease risks, are likely different among independent producers and operations utilizing some form of production contracts. Using results from a 2017 survey of U.S. hog producers, we estimate the effects of production contract use on adoption of enhanced biosecurity practices. The main result of this chapter is that contracting producers are more likely to adopt biosecurity. We find evidence that the effect of production contracts is heterogeneous across enterprise types. Chapter 2: The Market for Traceability with Applications to U.S. Feeder Cattle. For voluntary traceability programs, a key interest for program designers and policymakers is how to encourage participation. We contend that participating in voluntary traceability can be viewed as a product characteristic, and thus serves as a source of product differentiation. We study the implicit market for traceability systems for the first known time. In our empirical example, we use stated choice experiments to link feeder cattle sellers and buyers through premiums and discounts for cattle traceability systems. Using results from discrete choice models, we simulate changes in traceability supply and demand in response to prices and policies. We find that cost-share policies might be an effective way of encouraging participation for feeder cattle sellers and could serve as an alternative to mandating traceability. Chapter 3: Cow-Calf Producer Willingness to Report Disease: A Test of Adverse Selection. Animal health agencies' efforts to prevent and control foreign animal disease outbreaks depend on, among other factors, timely livestock producer self-reporting of disease suspicions. Adverse selection applies to disease reporting because livestock producers have private information about their disease status. Policymakers want to know how to set policy variables such that producers reveal private information about disease status, early, before the disease spreads. In this chapter, we study the effects of disease prevalence and indemnity payments on cow-calf producer willingness to report foot-and-mouth disease (FMD) suspicions. A novel test of adverse selection arises because we can determine how the rate of disease reporting adjusts to policy variables evaluated at different disease prevalence rates. Producers that report FMD suspicions do so early such that the effects of policy variables diminish at high prevalence rates.
Keywords: Biosecurity; Traceability; Livestock economics